Remoção de cianobactérias de águas por processo de flotação por ar dissolvido - Oliveira, Gislayne Alves (2016)
Human activities generate qualitative and quantitative impacts of water resources which vary in intensity with the occupation and urbanization of a watershed, create a big problem due to the high concentration of nutrients. The nutrients released into waterways, when they exceed the limit self-purification of water resources can cause algal blooms and the development of cyanobacteria, which can be toxic organisms and has been negatively highlighting the water treatment system for public supply. This is because the conventional treatments are not effective for the removal of the cyanobacteria, and cause harmful effects to human health, but often the conditions are more precarious not occurring treatment before consumption. Many chemical agents used in the treatment can be reacted with cyanobacteria, causing cell lysis (breakage) worsening the dispersion of toxins in water. Accordingly, it was evaluated the removal efficiency of Dolichospermum cylindrica cyanobacterial species, as well as identify the best operating conditions and comparison of the application of natural coagulant - tannin with aluminum sulfate, using dissolved air flotation (DAF). The experiments were developed in bench scale using the equipment: pitchers test (coagulation / flocculation) and the bench flotation (DAF). The tests were conducted at different phases when using the two tested coagulants. In the first step we tried to determine the zeta potential of cyanobacteria, in the second part we build the coagulation diagram (pH coagulation x coagulant dosage), followed by flocculation tests which sought better results for the velocity gradient (Gf) and time flocculation (Tm) and at the end evaluate the FAD testing the design parameters such as saturation pressure (Psat), recirculation rate (R) and flotation velocity (Vf). The performance of the treatment system was evaluated from the cell count. The results show that the cells of cyanobacteria had no change in zeta potential in relation to different pH ranges, and negative behavior ranging from -25.7 to -20.1 mV. In the construction of the coagulation diagram aluminum sulfate coagulation showed a broad pH range (4.5 to 9), reducing a bit pH range when used as the tannin coagulant (6-9). Both coagulants showed excellent results using the DAF, but aluminum sulfate showed higher removal (97.93%), even with the lowest removal (87.97%) tannin ends up being more suitable for being biodegradable, and having adsorption capacity for metals in the water. In relation to the parameters of this design, it was noticed that it is better removal using aluminum sulphate Gf to 25 s-1, Tm 15 minutes, Psat 300 kPa, and R 10% Vf 2.5 cm.min-1 and tannin Gf 50 s-1, Tm 10 minutes, Psat 300 kPa, and R 15% Vf 2 cm.min-1. In general, FAD has shown good results for your application in the removal of cyanobacteria.